A novel solution-gated graphene transistor biosensor for ultrasensitive detection of trinucleotide repeats. Issue 14 (1st July 2020) - Ge, Zhiqi; Ma, Mingyu; Chang, Gang; Chen, Meijun; He, Hanping; Zhang, Xiuhua; Wang, Shengfu
Abstract : A novel SGGT biosensor is constructed to achieve highly sensitive and selective sensing of GAA TNRs by integrating G-quadruplex enzymes. Abstract : A new way to detect GAA trinucleotide repeats (TNRs) based on a solution-gated graphene transistor (SGGT) with high performance was developed. Friedreich's ataxia (FRDA) is a neurodegenerative disease where the first intron of the frataxin (FXN) gene exhibits an extended GAA repeat region. Herein, a SGGT biosensor was constructed based on G-quadruplex DNAzymes and graphene channels. The DNAzymes quantify the captured target DNA by producing a strong catalytic current signal depending on the peroxidase-like activity. The higher the target DNA quantity captured on the gate electrode is, the higher is the concentration of DNAzymes on the surface of the gate electrode, which generates a high catalytic current. Due to the excellent self-amplifying performance of the transistor, the current signal of the SGGT is several hundreds of times larger than in conventional electrochemistry under identical detection conditions. Moreover, a large current signal can be obtained in the case of a low concentration of H2 O2 when compared to the case of an enzyme-catalyzed transistor. The SGGT biosensor also exhibits an ultra-low detection limit (32.25 fM), a wide linear range (100 fM–100 nM), and excellent selectivity. The results show that the SGGT biosensor has great potential in the early diagnosis of neurodegenerative diseases.